A békés-csanádi szlovák parasztcsaládok csehszlovákiai letelepítése a lakosságcsere keretében : 1945-1948 - Kugler, József (Közép-Európai Közlemények, 2012)
In 1947 on April 12, that is now 65 years ago that actually, the Hungarian-Czechoslovakian population exchange has been started. 60 to 70 rail-car trains departed and arrived to the Slovaks and Germans inhabited settlements in Hungary and also to the villages and small towns of “Mátyus-föld” and “Csallóköz”, the places which were under Czechoslovak sovereignty that time. (The name of the above mentioned - mostly Hungarian-populated geographical area – was Slovak Lowland.) The trains transported all the movable properties (furniture, agricultural tools, livestock) of the families covered by the convention from one State to another. The relocation of the Slovaks in Hungary (as well known) was voluntary, while the Hungarian families living in the Highland were ordered to live their homeland by the Czechoslovak Government. The Slovak authorities wanted to move more and more hungarian slovak families with husbanding experiences in to the mentioned area, just to ensure the change of the ethnic composition of this region, to make sure of the continuity of agricultural production. The presentation analyzes the resettlements issues (in Slovaika) of the mentioned families and the locating difficulties of the Highland families arriving to Hungary.